THEORETICAL MODELING AND TEST SIMULATION RESEARCH OF DOUBLE-LAYER VIBRATION ISOLATION SYSTEM - CHEN GaoSheng; LAI LiangQing; JIANG HongGang; SU ZhengTao (Jixie qiangdu)
The theoretical model of double-layer vibration isolation system based on the icebox compressor was built through the four-point parameter method,and got the force transportation-rate pattern,found the finite element simulation model of double-layer vibration isolation,obtained the main mode of the system through mode analysis and the force transportation-rate through dynamic reaction analysis. The force transportation-rate results through theoretical model and finite simulation method and test were compared and analyzed,the results show,the natural frequencies obtained from the theoretical model and simulation model are basically same,the force transportation-rate has the same trend on the whole,the theoretical results and simulated results accord well with the test results in the low frequency between 0 to 150 Hz,when the frequency exceeds 150 Hz,there are some differences between theoretical results,simulation results and test results to some extent.